AN ANALYSIS OF TRANSLATION QUALITY ON FIGURATIVE LANGUAGE IN TERMS OF ACCURACY AND ACCEPTABILITY IN “COCO” MOVIE - Ika Oktaria Cahyaningrum (Universitas Sebelas Maret, 2022)
Translation is a process of transferring message from a source language into a target language. One of translation products is subtitling in the movie. Figurative language is also found in the movie. Therefore, translators should pay attention on translating figurative language in the movie. The researcher chose Coco movie because there are many figurative languages which found in the movie. This research is descriptive qualitative. A triangulation technique was employed in this research. The data are all figurative languages in Coco movie. The other data are taken from the questionnaires assessed by three raters. The total data of figurative language in the movie are 52 data. The analysis on the figurative language shows that there are six types of figurative language found in Coco movie. They are metaphor (4 data or 8%), simile (6 data or 12%), personification (24 data or 46%), metonymy (9 data or 17%), symbol (7 data or 13%) and hyperbole (2 data or 4%) The analysis on the translation accuracy shows that 42 data or 81% from the total data are accurate, 10 data or 19% are less accurate, and no datum is inaccurate. The analysis on the translation acceptability shows that 38 data or 73% from the total data are acceptable, 14 data or 27% are less acceptable, and no datum is unacceptable. Personification becomes the dominance type of figurative language because there are a lot of inhuman objects involved. On the other hand, hyperbole becomes the submissive type of figurative language because only few exaggeration dialogues used.